A comprehensive study on recycled and virgin PET melt-spun fibers modified by PMDA chain extender - Qu, Muchao; Lu, Dong; Deng, Hongyi; Wu, Qiang; Han, Lei; Xie, Zixin; Qin, Yijing; Schubert, Dirk W. (Materials Today Communications, 2021)
The effect of chain extender Pyromellitic dianhydride (PMDA) on the comprehensive properties of the virgin (vPET) and recycled Polyethylene terephthalate (rPET) fibers was investigated. Five different weight fractions of PMDA were melt mixed with PETs to create long-chain branched (LCB) structures. The modified LCB-PET granules were melt spun into fibers using a capillary rheometer at 270 and 280 °C, and then aerodynamically stretched by an aspirator at seven take-up pressures. The different shear viscosity, thermal properties and spinnability of LCB-vPET and LCB-rPET, and the surface morphology, draw ratios, tenacity, elongation at break of PET fibers, as well as the performance-reliability plots using Weibull distribution were well discussed. A semi-empirical mathematical model further confirmed the exponential relationship between the tenacity and elongation at break of the PET fibers. This research depicts a visible window for academic and industrial researchers to produce PMDA modified PET fibers with desirable comprehensive properties.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Chain Extender; Modeling; PET fibers; PMDA; Weibull Distribution